Akulturasi Islam Dan Budaya Lokal (Studi Kasus Tradisi Sedekah Bumi Di Desa Karang Ploso Kecamatan Plandaan Kabupaten Jombang) - Qurrotul Ainiyah; Ayu Mira Mardani (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
This study aims to determine the acculturation of Islamic value in Sedekah Bumi in Karangmojo village Plandaan Jombang. Type of field research with a qualitative approach. The technique of collecting data is by interview, observation and documentation. Data analysis includes reduction, presentation, drawing conclusions and verification. The validity test of the data is done by triangulating techniques and sources. Sedekah Bumi in Karangmojo Village Plandaan Jombang is one of the traditional descending rituals as a symbol of respect for the land that is the source of life and gratitude to the Creator who has provided rizki, prosperity and safety. A variety of foods are available to eat and offered to punden which is enlivened by the appearance of local culture. Keywords: Islamic acculturation, local culture, Sedekah Bumi tradition